Handbook of Mechanics of Materials - Schmauder, Siegfried; Chen, Chuin-Shan.; Chawla, Krishan K.; Chawla, Nikhilesh; Chen, Weiqiu; Kagawa, Yutaka; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides a comprehensive reference for the studies of mechanical properties of materials over multiple length and time scales. The topics include nanomechanics, micromechanics, continuum mechanics, mechanical property measurements, and materials design. The handbook employs a consistent and systematic approach offering readers a user friendly reference ideal for frequent consultation. It is appropriate for an audience at of graduate students, faculties, researchers, and professionals in the fields of Materials Science, Mechanical Engineering, Civil Engineering, Engineering Mechanics, and Aerospace Engineering.
Dislocation nucleation mediated plasticity of FCC nanowires -- Indentation behaviour of metallic glass via molecular dynamics simulation -- Surface/Interface Stress and Thin Film Stress -- On the vibratory probing of atomic force microscopy -- Characterization of mechanical properties in polymeric materials: A bottom-up approach -- Fracture nanomechanics -- In situ Transmission Electron Microscopy Investigation of Dislocation Interactions -- Multiscale Modeling of Radiation Hardening -- Atomistic simulations of Metal/Al2O3 interfaces -- Multiscale simulation of precipitation in copper-alloyed pipeline steels and in Cu-Ni-Si alloys -- Atomistic simulations of hydrogen effects on lattice defects in alpha iron -- Molecular Dynamics Simulations of Nanopolycrystals.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Nanoscience; Materials; Civil engineering; Aerospace engineering; Astronautics; Solid Mechanics; Characterization and Analytical Technique; Nanophysics; Materials Engineering; Civil Engineering; Aerospace Technology and Astronautics